Necrosulfonamide Alleviates Acute Brain Injury of Intracerebral Hemorrhage via Inhibiting Inflammation and Necroptosis - Zhang, Xiangyu; Zhang, Yan; Wang, Fei; Liu, Yang; Yong, V. Wee; Xue, Mengzhou (Frontiers in Molecular Neuroscience, 2022)
Objective: Intracerebral hemorrhage (ICH) is the most lethal subtype of stroke, without effective treatment. Necrosulfonamide (NSA), a specific inhibitor for mixed lineage kinase domain-like protein, has been reported to exert neuroprotective effects in neurological diseases by ameliorating neuroinflammation and necroptosis. We hypothesized that NSA would alleviate acute brain injury and improve behavioral outcomes after ICH. Methods: Male adult C57BL/6 mice were assigned randomly into three groups. In vehicle and treatment groups, animals were injected collagenase VII to induce ICH. The solvent (0.25% DMSO) and NSA (5 mg/kg) were administrated intraperitoneally twice a day, respectively. The sham group was injected with saline and administrated with DMSO. The brain hematoma volume, inflammatory factors, and blood-brain barrier permeability were measured at 3 d after the operation. Fluorescent double immunostaining was performed to evaluate neuronal death. Neurological functions were assessed. Results: In the NSA group, the hematoma size was significantly reduced, inflammatory cells and cytokines were suppressed, and blood-brain barrier was protected compared to vehicle controls. NSA dramatically reduced the death of neurons, and improved performance of neurological functions after ICH. Conclusions: NSA has a neuroprotective role in alleviating acute brain injury in a mouse ICH model, and this is associated with reduced neuroinflammation and necroptosis.